Antagonism of the Interferon-Induced OAS-RNase L Pathway by Murine Coronavirus ns2 Protein Is Required for Virus Replication and Liver Pathology - Zhao, Ling (Elsevier Inc., 2012)
Many viruses induce hepatitis in humans, highlighting the need to understand the underlying mechanisms of virus-induced liver pathology. The murine coronavirus, mouse hepatitis virus (MHV), causes acute hepatitis in its natural host and provides a useful model for understanding virus interaction with liver cells. The MHV accessory protein, ns2, antagonizes the type I interferon response and promotes hepatitis. We show that ns2 has 2′,5′-phosphodiesterase activity, which blocks the interferon inducible 2′,5′-oligoadenylate synthetase (OAS)-RNase L pathway to facilitate hepatitis development. Ns2 cleaves 2′,5′-oligoadenylate, the product of OAS, to prevent activation of the cellular endoribonuclease RNase L and consequently block viral RNA degradation. An ns2 mutant virus was unable to replicate in the liver or induce hepatitis in wild-type mice, but was highly pathogenic in RNase L deficient mice. Thus, RNase L is a critical cellular factor for protection against viral infection of the liver and the resulting hepatitis.